PENGARUH GAYA KEPEMIMPINAN, LINGKUNGAN KERJA, GAYA KEPEMIMPINAN DAN KOMPENSASI BAGI HASIL TERHADAP LOYALITAS KARYAWAN DI CAFE TERAS RUMAH NENEK - Syahbudin, Muhammad Daffa; Sardiana, Anna (Journal of Accounting, Management and Islamic Economics, 2024)
The increasingly advanced economic development in Indonesia has made many people try to make businesses with various patterns. In line with the rampant business development, several business concepts have also developed, one of which is the concept of profit sharing. This study uses a descriptive research design approach with empirical data collected through an online survey of samples of Teras Rumah Grandma employees. The empirical data was then processed using the Structural Equation Modeling approach to test a number of hypotheses proposed. The results of the conclusions of this study are as follows: 1) Work environment variables have a positive and significant effect on employee loyalty. 2) The leadership style variable has a positive and significant effect on employee loyalty. 3) The variable of profit sharing compensation has a positive and significant effect on employee loyalty.